PERAN GURU DALAM MENERAPKAN PENDEKATAN ETNOPEDAGOGI DI SEKOLAH DASAR : LITERATUR REVIEW: LITERATUR REVIEW - sarbaini, Weni; Atania Rosbina Br Bangun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of teachers in implementing the ethnopedagogical approach in primary schools, emphasizing the teacher’s functions as a facilitator, cultural transformer, and learning innovator. Using a literature study method, this research systematically reviews scientific sources such as journal articles, books, and conference proceedings published between 2020 and 2025. The results indicate that ethnopedagogy plays a crucial role in enhancing students’ learning motivation, shaping character, and strengthening cultural identity within the primary education context. However, its implementation still faces significant challenges, including teachers’ limited competence in understanding and applying ethnopedagogical principles, the lack of culturally based learning materials, and insufficient institutional and policy support from educational authorities. Therefore, sustainable policy intervention is required through teacher training, the development of contextual learning modules, and collaborative partnerships among schools, communities, and local governments. Ethnopedagogy holds strategic potential as a transformative educational approach that promotes character building, cultural identity, and contextually relevant learning aligned with the demands of the 21st century.